Co-creating health: navigating a design for health collaboration. Issue 2 (28th July 2020) - Nakarada-Kordic, Ivana; Kayes, Nicola; Reay, Stephen; Wrapson, Jill; Collier, Guy
Abstract: We drew on the principles of co-autoethnography to explore the experiences of two multidisciplinary university-based teams engaged in design for health work: (1) a design team embedded in a hospital consisting of designers and social researchers; and (2) a person-centred rehabilitation research team of health researchers and professionals. We explored 'how might our experience of working in design for health inform how we work more effectively together?' Written reflections provided by contributors from each team and a transcript of a group discussion were analysed drawing on conventional content analysis. We identified that design for health collaborations are often surrounded by substantial challenges and tensions that are perpetuated through: (1) A clash of worlds and disciplines; and (2) Constraining systems and structures. A shared sense of excitement, hope, and passion for the possibility that a design for health collaboration brings were also identified, as was the need for risk-taking. This work will have practical utility for those commencing work in this complex, transdisciplinary space. We propose successful design for health collaborations are conditional on three core processes: (1) Understanding psychosocial contexts; (2) Building connectivity; and (3) Building capability. These should be enacted through collaborative discussion at the initiation of each new collaborative project.